Browne's immanent critique of the perspectives of Habermas and Giddens: philosophy of praxis, contemporary modernity and social classifications: Habermas and Giddens on praxis and modernity. A constructive comparison, by C. Browne, London, Anthem Press, 2017, 314 pp., £70.00, ISBN 9781783085002. (4th May 2021) - Bialakowsky, Alejandro
ABSTRACT : This review article reconstructs and analyses Browne's book Habermas and Giddens on Praxis and Modernity. A constructive comparison. To that end, in principle, it address the manner in which Giddens's and Habermas's perspectives and intellectual careers at various points in their work conceptualize and take part in certain epochal and theoretical crossroads: the tensions of the welfare state, the 'triumph' of neoliberalism and the revision of Marxism. Then, Browne's comparative study on both perspectives – which specifies their contributions, shortcomings and respective 'potential' concepts – is traced. Following that, the methodological dimension of the book is displayed, inasmuch as it is a methodological reflection on the theoretical research. Thus, a key relationship between the 'comparative-constructive' research method and Browne's view of critical theory is observed: an immanent critique regarding the theoretical-analytical problem of the philosophy of praxis. Lastly, points of contact are identified between the elaborations in the book and a reflection on the processes of sociological and social reclassification in the perspectives of Giddens and Habermas with respect to the possibilities of mutual practical transformations between social spaces in general and the conceptualizations and inquiries of sociology and social theory.